Numerical Heat Transfer Investigation in a Heat Exchanger Tube with Hexagonal Conical-ring Inserts - Sripattanapipat, Somchai; Tamna, Sombat; Jayranaiwachira, Nuthvipa; Promvonge, Pongjet (My University, 2016)
The hexagonal conical rings (HCR) modified from the typical conical ring (CR) are used as a turbulence promoter for producing the vortex flows to enhance the heat transfer rate in a heat exchanger tube. To reduce the pressure loss, the V-shaped HCR (V-HCR) obtained by cutting both symmetric plane of the cone-tip of HCR at 30°, 45°and 60°is offered in the present work. The tube fitted with V-HCR elements having a fixed inlet and outlet diameter is numerically investigated. The computation is carried out for Reynolds number in a range of 3000 to 20,000 in a uniform heat-fluxed test tube. The numerical results show that the V-HCR insert leads to much higher heat transfer than the typical CR/HCR insert or the smooth tube alone and also provides lower friction factor. The 30°V-shaped HCR gives the highest heat transfer and thermal performance due to the lowest friction loss, indicating the promising device of the V-HCR.
Keywords: Conical ring; Heat exchanger; Heat transfer; Turbulent flow; Vortex generator